The sub/supra‐optimal temperature‐induced inhibition of photosynthesis and oxidative damage in cucumber leaves are alleviated by grafting onto figleaf gourd/luffa rootstocks. Issue 3 (23rd May 2014) - Li, Hao; Wang, Feng; Chen, Xiao‐Juan; Shi, K; Xia, Xiao‐Jian; Considine, Michael J; Yu, Jing‐Quan; Zhou, Yan‐Hong
<x xml:space="preserve">Abstract</x> Shoot‐root communication is involved in plant stress responses, but its mechanism is largely unknown. To determine the role of roots in stress tolerance, cucumber (Cucumis sativus) shoots from plants with roots of their own or with figleaf gourd (Cucurbita ficifolia, a chilling‐tolerant species) or luffa (Luffa cylindrica (L.) M. Roem., a heat‐tolerant species) rootstocks were exposed to low (18/13°C), optimal (27/22°C) and high (36/31°C) temperatures, respectively. Grafting onto figleaf gourd and luffa rootstocks significantly alleviated chilling and heat‐induced reductions, respectively, in biomass production and CO2 assimilation capacity in the shoots, while levels of lipid peroxidation and protein oxidation were decreased. Figleaf gourd and luffa rootstocks upregulated a subset of stress‐responsive genes involved in signal transduction (MAPK1 and RBOH), transcriptional regulation (MYB and MYC), protein protection (HSP45.9 and HSP70), the antioxidant response (Cu/Zn‐SOD, cAPX and GR), and photosynthesis (RBCL, RBCS, RCA and FBPase) at low and high growth temperatures, respectively, and this was accompanied by increased activity of the encoded enzymes and reduced glutathione redox homeostasis in the leaves. Moreover, Heat Shock Protein 70 (HSP70) expression in cucumber leaves was strongly induced by the luffa rootstock at the high growth temperature but slightly induced by the figleaf gourd rootstock at low or high growth temperatures. These results indicate that rootstocks could induce significant changes in the transcripts of stress‐responsive and defense‐related genes, and the ROS scavenging activity via unknown signals, especially at stressful growth temperatures, and this is one of mechanisms involved in the grafting‐induced stress tolerance.